Feasibility Study of Purse Seine Business Units In Tanete Riattang Timur Sub-District Bone District - Rian, Andi Adrian Dwi Nugraha; Fakhriyyah, Sitti; Cangara, Arie Syahruni (PONGGAWA : Journal of Fisheries Socio-Economic, 2022)
In general, coastal communities in Tanete Riattang Timur Subdistrict in fulfilling their daily needs work in the marine and fisheries sector. The most widely used fishing gear is the Purse Seine and has constraints both in terms of finance, technology and business competition, the purse seine fishing community still maintains patterns of the economic system in fishing activities as a reference material in living their daily lives so that the purse fishing business The seine needs to be calculated for its financial feasibility to determine its sustainability in the future. In general, this study aims to determine the level of income from production activities and the level of business feasibility of purse seine fishermen to be developed in Tanete Riattang Timur District. This research was conducted from April to May 2021. In this study, the method used is descriptive quantitative with data analysis using income analysis = TR – TC and Business Feasibility Analysis with the formula Net B/C ratio = NVP(+)/NVP( -). The purse seine business unit has a Net B/C value greater than 1 (3.90 > 1) which is obtained from the Nvp (+) value divided by the Nvp (-) value, the purse seine business unit has an Npv value of 4,034,338,574 and the interest rate of return bank (IRR) of 86%. this means that the purse seine fishing business is feasible to carry out and continue.